Entrepreneurship Practicum Learning and Entrepreneurial Intention amongUniversity Students: The Sequential Mediating Roles of EntrepreneurialMindset and Self-Efficacy - Yudi Siyamto; Indah Piliyanti; Mochamad Rofik (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
This study aims to examine the effect of entrepreneurship practicum learning on entrepreneurial intention through entrepreneurial mindset and entrepreneurial self-efficacy as serial mediators. Although entrepreneurship practicum learning has increasingly been implemented in higher education, the psychological mechanisms that explain how this type of learning shapes entrepreneurial intention remain relatively underexplored. The study employed a quantitative explanatory design involving 157 students participating in entrepreneurship practicum courses. Data were collected using a structured questionnaire and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings indicate that entrepreneurship practicum learning positively affects entrepreneurial intention and entrepreneurial mindset. An entrepreneurial mindset was also found to positively influence entrepreneurial self-efficacy, while entrepreneurial self-efficacy significantly affected entrepreneurial intention. In addition, entrepreneurial mindset and entrepreneurial self-efficacy sequentially mediated the relationship between entrepreneurship practicum learning and entrepreneurial intention. These findings suggest that entrepreneurship practicum learning contributes to entrepreneurial intention through interconnected psychological mechanisms involving entrepreneurial mindset and entrepreneurial self-efficacy. The study extends entrepreneurship education literature by highlighting the complementary roles of Experiential Learning Theory, Social Cognitive Theory, and the Theory of Planned Behavior in explaining entrepreneurial intention among university students.